Substance P- and choline acetyltransferase immunoreactivities in somatostatin-containing, human submucosal neurons - Beyer, Jakob; Jabari, Samir; Rau, Tilman T.; Neuhuber, Winfried; Brehmer, Axel (Histochemistry and Cell Biology, 2013)
The submucous layers of human small and large intestines contain at least two separate neuron populations. Besides morphological features, they differ in their immunoreactivities for calretinin (CALR) and somatostatin (SOM), respectively. In this study, submucosal wholemounts of 23 patients or body donors (including all segments of small intestine and colon) were immunohistochemically quadruple stained for CALR and SOM as well as for substance P (SP) and choline acetyltransferase (ChAT). We found that all SOM-positive neurons co-stained for ChAT and the majority for SP [between 50 % in the small intestinal external submucosal plexus (ESP) and 75 % in the colonic ESP]. In contrast, a majority of CALR-neurons contained ChAT (between 77 % in the small intestinal ESP and 92 % in the large intestinal ESP) whereas less than 4 % of CALR-neurons were co-immunoreactive for SP. Another set of wholemounts was co-stained for peripherin, a marker enabling morphological analysis. Where identifiable, both SOM alone- and SOM/SP-neurons displayed a uniaxonal (supposed pseudouniaxonal) morphology. We suggest that the chemical code of SOM-immunoreactive, human submucosal neurons may be "ChAT+/SOM+/ SP±". In additional sections double stained for SOM and SP, we regularly found double-labelled nerve fibres only in the mucosa. In contrast, around submucosal arteries mostly SOM alone- fibres were found and the muscularis propria contained numerous SP-alone fibres. We conclude that the main target of submucosal SOM(/SP)-neurons may be the mucosa. Due to their morpho-chemical similarity to human myenteric type II neurons, we further suggest that one function of human submucosal SOM-neurons may be a primary afferent one. © 2013 Springer-Verlag Berlin Heidelberg.
Keywords: Enteric nervous system; Gut; Innervation; Mucosa; Submucosal plexus